Diagnostic Value of Plasma miR-181b, miR-196a, and miR-210 Combination in Pancreatic Cancer. (6th August 2020) - Liu, Gongpan; Shao, Cunhua; Li, Anyun; Zhang, Xiaobin; Guo, Xingjun; Li, Jiangong
Abstract : Purpose . This study was aimed at investigating the roles of plasma miR-181b, miR-196a, and miR-210 in the diagnosis of pancreatic cancer (PC). Methods . Plasma samples were isolated from 40 patients with PC and 40 healthy individuals, respectively. The expression of miR-181b, miR-196a, and miR-210 was detected by qRT-PCR. The level of carbohydrate antigen 199 (CA199) was measured by an electrochemiluminescence (ECL) assay. The receiver operating characteristic (ROC) curve was used to analyze the diagnostic value of miR-181b, miR-196a, miR-210, CA199, and their combinations in PC. Results . The expression of plasma miR-181b, miR-196a, and miR-210 was significantly upregulated in PC patients. The plasma level of CA199 was also significantly increased in PC patients. The expression of miR-181b, miR-196a, and miR-210 was closely associated with lymph node metastasis, clinical stage, and vascular invasion but not correlated with age, gender, and tumor size. miR-181b, miR-196a, and miR-210 have lower AUC than CA199 in the diagnosis of PC. miR-181b+miR-210 and miR-196a+miR-210 also have lower AUC than CA199. It is worth noting that miR-181b+miR-196a+miR-210 has a higher AUC than CA199 in the diagnosis of PC. Conclusion . The combination of plasma miR-181b, miR-196a, and miR-210 had a good diagnostic value for PC.